Safety of switching from natalizumab straight into fingolimod in a group of JCV-positive patients with multiple sclerosis - Fragoso, Yara Dadalti; Alves-Leon, Soniza Vieira; Becker, Jefferson; Brooks, Joseph Bruno Bidin; Correa, Eber Castro; Damasceno, Alfredo; Gama, Paulo Diniz da; Gama, Rodrigo Assad da; Matta, Andre Palma da Cunha; Maciel, Ernane Pires; Cristina d’Avila Winckler, Thereza (Arquivos de Neuro-Psiquiatria, 2016)
Objective To assess safety of the switch between natalizumab and fingolimod without a washout period.Methods Prospective data on 25 JCV positive patients who underwent this medication switch were collected and analyzed.Results After a median period of nine months from the medication switch, there were no safety issues to report. The patients had good disease control and no adverse events were reported.Conclusion Washout may not be necessary in daily practice when switching from natalizumab to fingolimod. Expertise on multiple sclerosis management, however, is essential for drug switching.
Keywords: multiple sclerosis; natalizumab; fingolimod hydrochloride; therapeutics